Synergistic Activity of Cinnamomum burmannii (Nees & T. Nees) Blume and Aquilaria malaccensis Lamk. Extracts for Antidiabetic Study - Aden Arrafif Bahtiarsyah; Lisna Hidayati; Nastiti Wijayanti; Tri Rini Nuringtyas (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Type 2 diabetes mellitus affects glucose metabolism resulting in hyperglycemia. The bark of Cinnamomum burmannii (CB) and the leaves of Aquilaria malaccensis (AM) are believed to be effective for diabetes treatment. This study evaluated the synergistic effect of CB and AM extracts, the extracts' phytochemical profiles, and interaction between CB and AM metabolites with a-glucosidase through molecular docking.METHODS: The dried material was macerated with ethanol and then tested for a-amylase and a-glucosidase inhibitory activities and glucose diffusion inhibition in varied combination proportions. The extract fingerprinting was performed using a UV-Vis spectrophotometer followed by thin layer chromatography to determine the class of secondary metabolite in the extracts. Human maltase-glucoamylase (MGAM) receptor, ligands from acarbose and selected metabolites of CB and AM were studied in silico using UCSF Chimera, AutoDockTools, Autodock Vina Wizard (PyRx), and Biovia Discovery Studio software.RESULTS: The best ratio of CB:AM extracts for a-amylase and a-glucosidase inhibition was 0.75:0.25 mg/mL, with inhibitory activities of 86.36 and 96.38 %, respectively. The best glucose diffusion inhibition was achieved at a ratio of 0.5:0.5 mg/mL CB and AM extracts. The b-caryophyllene of CB and palustrol of AM had a significantly higher binding affinity of -10.7 kcal/mol and -10.2 kcal/mol, respectively than acarbose, which had a binding affinity of -8.1 kcal/mol.CONCLUSION: A correct ratio of CB to AM extracts suppresses the activity of diabetes-related enzymes more efficiently. The in silico study suggested that the presence of b-caryophyllene in CB and palustrol in AM supported the synergistic activity.KEYWORDS: Aquilaria malaccensis, Cinnamomum burmannii, diabetes mellitus, α-amylase inhibition, α-glucose inhibition, glucose inhibition